(untitled) (International Journal of Scientific Pediatrics, 2026)
Introduction. Retrochorial hematoma (RCH) in early gestation in women can predict adverse maternal, fetal, and neonatal outcomes. The relationship between the presence of RCH, its location, size, and perinatal complications was studied. Increased RCH size is associated with an increased risk of pregnancy complications such as vaginal bleeding in the first trimester, early fetal loss, fetal growth restriction, placental abruption, and preterm labor. The aim of this study was to investigate the association between first-trimester retrochorial hematoma and gestational and perinatal complications. Patients and methods. Information on 177 patients whose pregnancies in the first trimester (<14 weeks) were complicated by retrochorial hematoma was obtained from an analysis of archival material at Tashkent Regional Clinical and Practical Center No. 6, conducted between January 2023 and December 2025. A control group (35 healthy pregnant women) was recruited from the outpatient clinic of this institution. The presence of fetal cardiac activity at the time of diagnosis of retrochorial hematoma was a prerequisite for inclusion in the study. Depending on the hematoma size, pregnant women with RCH were divided into three groups: with small hematomas (RCH-I group, n = 57), with medium hematomas (RCH-II group (n = 101) and with large hematomas (RCH-III group, n = 19). The control group consisted of 35 pregnant women without RCH and vaginal bleeding. Statistical processing of the data was performed within the framework of a retrospective study using Statistica software (version 25.0). Results. Retrochorial hematoma is associated with an increased frequency of bleeding in the first trimester, regardless of its size, as well as with a lower gestational age of the fetus at delivery. At the same time, an increase in the size of a retrochorial hematoma increases the risk of placental abruption, preterm labor, SIDS and fetal loss. Conclusions. Thus, the association of early gestation retrochorial hematoma with The association of retrochorial hematoma with maternal, fetal, and neonatal complications is widely discussed and requires further research aimed at identifying common pathogenetic mechanisms of retrochorial hematoma and adverse pregnancy outcomes, particularly fetal growth restriction syndrome.